Morphology of mitochondrial network in disseminated endometriosis cells in spontaneous pneumothorax diagnostic process: Mitochondria, endometriosis and pneumothorax - Klezl, Petr; Svobodova, Pavla; Pospisilova, Eliska; Maly, Vilem; Bobek, Vladimir; Kolostova, Katarina (Cellular and Molecular Biology, 2024)
Circulating endometrial cells (CECs) have emerged as a new biomarker of advanced disease in women with endometriosis. The identification of several subtypes of CECs (e.g., stem cell-like, epithelial, glandular, stromal) has opened the way for characterization of endometriosis-associated CECs. This study focused on the isolation and characterization of CECs and disseminated endometrial cells (DECs) in patients with spontaneous pneumothorax (SP). The primary objective was to differentiate between cancer and non-cancer cells in patients with no previous cancer diagnosis. The MetaCell® size-based separation protocol was used to enrich CECs/DECs. Evaluation of the captured cells by 3D microscopy was performed using a NANOLIVE™ microscope using a holographic approach. Based on gene expression analysis (GEA), we can conclude that mitochondria are much more active in primary tumors compared to endometriosis tissue (e.g. MT-ND1, MT-ATP6 genes). The culture of DECs is made of stromal, stem and immune cells. In vitro culture of DECs is characterized by an increase in the epithelial marker KRT18. Similarly, NFE2L2, a proerythroid factor, is also elevated. Further, a significant decrease in the amount of stem and immune cells was observed in the cell culture of DECs. The data presented here show how morphologically plastic the changes in the mitochondrial network can be and how cells can reflect them at the level of gene expression. The markers identified could help in the accompanying diagnostic process of the spontaneous pneumothorax in women of reproductive age.